Adult Presentation of Anomalous Left Coronary Artery from the Pulmonary Artery with Severe Mitral Valve Regurgitation from Flail Posterior Leaflet - Digvijay D Nalawade; Prakyath Shetty; Anirudha Sadgir; Sanket Bari (Journal of the Practice of Cardiovascular Sciences)
Anomalous left coronary artery from the pulmonary artery (ALCAPA) is a rare congenital coronary anomaly, which usually presents in infancy, and survival to adulthood is very rare, around 10–15%. We report a 46-year-old female with no risk factors, who presented with a history suggestive of acute left heart failure of two weeks duration. Echocardiography revealed acute severe mitral regurgitation (MR) with flail posterior mitral leaflet (PML) due to chordae tendinae rupture (CTR) with normal left ventricular function and dimensions. There were no features suggestive of infective endocarditis, rheumatic or myxomatous affection of mitral valve. During preoperative workup, coronary angiography revealed the presence of ALCAPA which was confirmed by computed tomography. The patient underwent successful surgical repair of ALCAPA along with mitral valve replacement. The case underscores unusual association of ALCAPA in an adult age with acute severe MR secondary to flail PML due to CTR with a possible ischemic causal relationship.